CONSTIPATIONS IN CHILDREN - A. R. Polishchuk; S. I. Erdes; B. O. Matsukatova ("Paediatrician" Publishers LLC, 2012)
The questions of childhood constipations epidemiology, complications frequency and some statements of foreign conciliatory recommendation are discussed in this article. The authors show data on prevalence of this disorder in various countries. The importance of control of the clinical manifestations, which can be evidences of organic disorder, is highlighted. Also the authors pay special attention to age specificities of constipations development in children. The mechanisms and peculiarities of lactulose actions, indications and contraindications to its usage are discussed in detail. The article includes the data obtained from randomized clinical trials.